Fatty Acid and Tocopherol Contents of Several Seed Oils - Matthaus, B.; Musa Özcan, Mehmat; Al-Juhaimi, Fahad (Asian Journal of Chemistry, 2014)
The oil content of seeds ranged from 14.4 [sumac (Rhus coriaria) Siirt] % to 49 (Californium) % of the dry weight. The fatty acid composition of each rape and canola seed oils have the typical fatty acid composition for conventional rape and canola seed including 3.7-24.3 % of palmitic acid in addition to stearic acid (1.4-5.7 %), oleic acid (11.5-61.5 %), linoleic acid (16.7-75 %) and linolenic acid (0.1-9.9 %) as main components. The total fatty acids compositions of seed oils varied between 95.3 % (Sunflower Aydin202) to 99.9 % (Smart). As shown, the major tocopherol in the seed oils of rape and canola cultivars were a-tocopherol (3.4-56.3 %) and g-tocopherol (0.2-32.7 %) accompained by a-tocotrienol (0.0-4.8 %) and p8 (0.0-2.9 %).